2010
DOI: 10.4161/oxim.3.4.12860
|View full text |Cite
|
Sign up to set email alerts
|

Age Associated Oxidative Damage in Lymphocytes

Abstract: Lymphocytes are an important immunological cell and have been played a significant role in acquired immune system; hence, may play in pivotal role in immunosenescence. Oxidative stress has been reported to increase in elderly subjects, possibly arising from an uncontrolled production of free radicals with aging and decreased antioxidant defenses. This study was aimed to evaluate the level of lipid-protein damage and antioxidant status in lymphocytes of healthy individuals to correlate between oxidative damage … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
43
0
4

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(47 citation statements)
references
References 49 publications
0
43
0
4
Order By: Relevance
“…The average MDA level was 12.35 ± 0.37 nmol/mg protein in the group of young persons (11-20 years old) and increased with age reaching the highest average value of 33.63 ± 0.42 nmol/mg protein in the group of elderly persons (51-60 years) [16].…”
Section: Lipid Peroxidationmentioning
confidence: 87%
“…The average MDA level was 12.35 ± 0.37 nmol/mg protein in the group of young persons (11-20 years old) and increased with age reaching the highest average value of 33.63 ± 0.42 nmol/mg protein in the group of elderly persons (51-60 years) [16].…”
Section: Lipid Peroxidationmentioning
confidence: 87%
“…There are many studies on the change of SOD activity with aging, but the results reported are inconsistent, or even contradictory. Decreases in SOD1 have been observed in various tissues or cells from old human subjects in comparison with that from young adults, including skin fibroblasts [63, 64], lymphocytes [65], skeletal muscles [66], serum [67], plasma and erythrocytes [68, 69]. Animal studies also showed an age-dependent decrease in SOD1 activity in liver [70, 71], and brain [72, 73] of old rats.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore this assay usually gives an overestimation of free radical damage [Cherubini et al, 2005]. The authors generally avoid interferences by using different methods: Kwiecieñ et al, 2002, used BHT (butylated hydroxytoluene) to prevent further oxidation of the sample; deproteinisation was performed with trichloracetic acid [Cassini et al, 1986], forced the lipoperoxidation and stopped the reaction with SDS and acetic acid [Gautam et al, 2010;Ohkawa et al, 1979], added EDTA and refered the results to standards prepared from tetramethoxypropane [Houglum et al, 1990] or used the standard addition method [Sprinteroiu et al, 2010].…”
Section: Evaluation Of the End Products Of Lipid Peroxidationmentioning
confidence: 99%